Intercultural crisis communication during the 2011 Fukushima nuclear disaster - Yang, Aiyun (2014)
With the motivation of contributing to further development of the emerging field of intercultural crisis communication, the study aims at exploring the reasons why the global media criticized the Japanese authorities’ crisis communication during the 2011 Fukushima nuclear disaster through the inductive content analysis on both the Japanese authorities’ crisis communication and the global media’s perceptions on the Japanese authorities’ crisis communication. The data collected from 11 March to September 2011, including 160 press releases, transcripts of the foreign press conferences and speeches delivered at the international conferences by the Japanese authorities, and 120 news reports from BBC (89), Xinhua News Agency (19), and the New York Times (12), were analyzed. The findings reveal four main reasons for the criticism: (1) Fukushima nuclear disaster, which was a manmade disaster, could have been prevented; (2) radiation-related jargons were not explained sufficiently; (3) reassurance without detailed explanations was repeated frequently; (4) recognition of uncertainty was absent. The findings also unveil that stereotypes on Japanese culture possibly might be added to the above reasons. However, there is only one news report for that, which is not strong enough to confirm this hypothesis. Hence, the study offers a new insight into the theoretical or empirical study of crisis communication that the factor of stereotype may be considered when investigating the stakeholders’ perceptions. It also suggests the future research direction to further examine and test how stereotypes affect both the perceptions of stakeholders and the crisis response stance of responsible organizations or national authorities during crises.